Dynamics of indexes motive preparedness girls of junior classes - Худолій, О. М.; Мірошниченко, Д. Т. (Physical Education Theory and Methodology, 2012)
The article is sanctified to the study of dynamics of indexes of motive preparedness of girls of junior classes. It is set on the basis of data of experiment, that girls 8 show the best results in speed-power preparation and static endurance.